Noncommunicable disease risk factors among adolescent boys and girls in Bangladesh: Evidence from a National survey - Urmy, Nushrat Jahan; Hossain, Md. Mokbul; Shamim, Abu Ahmed; Khan, Md. Showkat Ali; Hanif, Abu Abdullah Mohammad; Hasan, Mehedi; Akter, Fahmida; Mitra, Dipak Kumar; Hossaine, Moyazzam; Ullah, Mohammad Aman; Sarker, Samir Kanti; Rahman, SM Mustafizur; et al. (Osong public health and research perspectives, 2022)
This article was published in Osong Public Health and Research Perspectives [©2020 Korea Disease Control and Prevention Agency. This is an open access article under the CC BY-NCND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).] and the definite version is available at: https://doi.org/10.24171/j.phrp.2020.11.6.03 The Journal's website is at: https://ophrp.org/journal/view.php?doi=10.24171/j.phrp.2020.11.6.03